Panrita Lamming dalam Perkawinan di Galesong Selatan Kabupaten Takalar - Hajrah Aisah; St. Junaeda (Rayhan Intermedia, 2023)
This study aims to: (1) find out the role of Panrita Lamming in marriage in the South Galesong community, (2) find out how the views of the South Galesong community are related to the existence of Panrita Lamming, and (3) find out the existence of Panrita Lamming in the modern era. This study uses qualitative data and is descriptive in nature. The data collection techniques were carried out using observation, interviews, and documentation methods involving as many as 8 informants. The results of this study indicate that: (1) Panrita Lamming is believed to have the advantages of prayer and knowledge so that he gets a role in society as traditional leader and ritual leader. (2) The community in general still believes in the benefits that can be obtained after using Panrita Lamming. Some people also think that this ritual is a habit of the parents that needs to be preserved, regarding whatever happens after the ritual is the power of Allah SWT. In addition, the public view from a religious perspective argues that this ritual is not in line with religious teachings, so it needs to be repaired or abandoned, and (3) The reasons for Panrita Lamming's continued existence are due to the growing belief in the ritual, and there is still confidence in the impact under Panrita Lamming.